(untitled) (Medico Legal Update, 2021)
The health care sector is currently facing twin burden, the impact of coexisting diseases as well as the pandemic of corona virus. The importance of commencing Neuro rehabilitation as early as possible is now well appreciated and accepted with adequate supporting evidence. However, it is also a fact that proper & prompt rehabilitation services are often deficient in majority of developing countries. With the everincreasing burden of those affected with the highly infectious disease COVID-19, venturing to Physiotherapy OPD for routine rehab care is not at all safe for the already vulnerable clients. At this point of time, family members can function as an extension of health care system by co-ordinating and contributing by participation, in the rehabilitation as directed by the therapist via telemedicine. Remote delivery of Physiotherapy through guided family-based approach is an ideal model to support on-going Physiotherapist’s services during this period, especially in the most vulnerable clients.